The impact of Family Medicine in medical undergraduate programs: apprenticeship centered in continuity and primary attention. The experience of the outpatient department of Family Medicine in PROMOVE - Adriana F. T. Roncoletta (O Mundo da Saúde)
The predominant model in education is still centered in intrahospital disciplines and environments. This model emphasizes the treatment of rare diseases and causes a lack of continuity in caring for diseases. What we frequently notice is a fragmentation in medical teaching. In accordance with the Brazilian Curriculum Guidelines, the Program of Family Medicine of University Center São Camilo provides students a longitudinal and integrative of care, which represents a new and innovatory approach where continuity is the basic principle. Part of the curriculum for the third year of the course, the discipline takes place every six months in the Clinical School PROMOVE, where students are under the supervision of a Family Doctor every week. Patients are assisted by the same pair and involved students are the reference for the patient they are in charge. Students say that they “feel like doctors”, and they have the opportunity of visiting the same patient several times and learn to simultaneously discuss clinical procedures and to emphasize the relationship patient-doctor, with a strong focus on communication techniques, essential skills for an ambulatory setting. This model allows students to incorporate the “core values” of Family Medicine: – the importance of seeing patients as a whole, the development of humanistic attitudes, and the construction of therapeutic relationships. Continuity favors learning in these aspects, and it also helps them to surpass stereotypes that might damage the empathy and precise clinical judgment, essential qualities for the development of professionalism. The preliminary results of this program may motivate institutions that want to develop similar programs. More studies are necessary to evaluate the long-term impact of these programs in medical education.